Microwave-Assisted Chemical Co-reduction of Pd Nanoparticles Anchored on Reduced Graphene Oxide with Different Loading Amounts - Dyah Ayu Fatmawati; Triyono Triyono; Wega Trisunaryanti; Uswatul Chasanah (Universitas Gadjah Mada, 2022)
Microwave-assisted Palladium/Reduced Graphene Oxide (Pd/RGO) synthesis was effectively carried out in this study, which looked at the effects of different Pd loading weights in Graphene Oxide (GO) on its physicochemical qualities. The Tour technique was used to make GO, with a KMnO4:graphite weight ratio of 3.5. Meanwhile, Pd/RGO was synthesized utilizing the in-situ reduction method of one-pot synthesis with ascorbic acid as the green reducing agent, yielding Pd-0.5/RGO, Pd-1.0/RGO, and Pd-2.0/RGO, respectively, with variations in Pd loading weight of 0.5, 1.0, and 2.0%. XRD, FTIR, SAA, SEM-EDX, and TEM were used to examine all material characterizations. As a result, Pd-1.0/RGO had the largest surface area of 65.168 m2/g among the Pd-based materials, with a pore volume of 0.111 cc/g, the pore diameter of 3.316 nm, Pd crystallite size of 28.29 nm, RGO nanostructure dimension of 3.37 × 28.53 nm, and reduction level (C/O) of 3.02. This material also contains specific functional groups, including O-H, C-H, CO2, C=C, C=O, and C-O, based on FTIR spectra. Therefore, optimal weight loading of metal on the surface of the supporting material will provide a large material surface area. Increasing the surface area of the material improves its performance as a catalyst.